Banker to the Poor : the story of the grameen bank - Yunus, Muhammad; Jolis, Alan (London : Aurum Press, 1999)
The book discusses how an economics professor from Bangladesh, trained in the U.S., goes back to his country to do "nation-building" and finds enormous untapped potential among the poor. The ability to create, not only a poverty alleviation strategy, but an organizational strategy that met with so much success was shown in the book.
Includes appendix and index
with a foreword by HRH the Prince of Wales
nmn 29/07/13
Loans
Keywords: Yunus, Muhammad; Grameen Bank; Banking - poor; Bangladesh